(untitled) (Bangladesh Journal of Medical Science, 2025)
Introduction Palliative care is a specialized area of healthcare focused on alleviating symptoms and improving the quality of life for patients with serious, life-threatening illnesses. This study explores the experiences of patients and nurses in a palliative care clinic, with the aim of identifying key factors influencing care quality and nurse satisfaction, such as the clinic environment, nurse-patient interactions, emotional stressors, and work conditions. Methods A qualitative design using thematic analysis was employed to examine feedback from 15 patients and 15 nurses working in a palliative care setting. Semi-structured interviews were conducted to gather insights into the participants’ experiences, which were analyzed using Braun and Clarke’s six-step process for thematic analysis. Results Thematic analysis revealed several key themes: (1) Clinic Environment and Accessibility, with mixed feedback on the remote location’s impact on family visits; (2) Nurse-Patient Interaction, highlighting concerns about nurse etiquette but affirming professional competence; (3) Work Stress and Emotional Demands on Nurses, including stress from patient non-compliance and emotional resilience; (4) Nurse Motivation and Career Satisfaction, where nurses expressed pride in their work despite the emotional challenges; (5) Recommendations for Improving Work Conditions, including calls for better compensation and support; and (6) Nurse- Patient Relationship and Care Quality, emphasizing the importance of empathy in improving patient outcomes. Conclusion The findings underscore the importance of addressing both environmental factors and interpersonal dynamics to enhance the quality of palliative care. Key recommendations include improving nurse training in communication, offering better emotional and financial support for staff, and fostering strong nurse-patient relationships. These strategies are crucial for improving both the care experience for patients and job satisfaction for nurses in palliative care settings. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 505-513